Analisis Faktor Tingkat Perkembangan Demokrasi di Indonesia Menurut Provinsi Tahun 2023 - Siti Nabila; Latifah Sekar Hanin; Sri Pingit Wulandari (PT PUSTAKA CENDEKIA GROUP, 2025)
Democracy is an important benchmark for assessing the progress of a country, especially in relation to the absence of social, economic, and political development. In Indonesia, variations in the level of democracy between regions reflect the influence of diverse social and economic aspects. The study of democracy in 2023 is very relevant in efforts to strengthen empowered communities and responsive governance. A comprehensive approach is needed to measure the level of democracy at the provincial level, with related variables such as community literacy index, open poverty rate, freedom, equality, and institutional capacity. This study uses principal component analysis (PCA) and factor analysis to identify the main components and spread the relationship between variables. The KMO test, Bartlett's test, and multivariate normality test were conducted to ensure the feasibility of the data. The results of the analysis show that the data meets the assumption of multivariate normal distribution as well as the criteria for independence and correlation between variables. Based on PCA, it was found that two main components were able to explain the variability of the data. The first component, namely social capacity building, includes four variables: literacy index, freedom, equality, and institutional capacity. The second component includes employment conditions as measured by the open poverty rate.